Comparing Political Leadership and Community Participation in Waste Governance in Banyumas, Indonesia and Alappuzha, India - Mahayasa, Dias Pabyantara Swandita; Saadah, Kholifatus; Utami, Arum Tri (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2026)
This study compares waste governance in Banyumas, Indonesia, and Alappuzha, India, two cities in the Global South that faced similar public health and environmental crises caused by waste accumulation and had access to comparable waste management technologies. Both cities received international recognition for their community-based systems, yet their policy trajectories diverged. Banyumas experienced stagnation, while Alappuzha achieved sustained progress. Using a most similar systems design (MSSD) framework, this paper highlights two variables that shape reform outcomes, political continuity and the institutionalization of community participation. In Alappuzha, stable political leadership and the Kudumbashree women’s cooperative transformed protests into formalized community participation. In contrast, Banyumas remained dependent on individual leadership and fragmented community groups, with weak institutionalization leaving reforms fragile and vulnerable to political turnover. These findings suggest that although both cities began from similar conditions, political capacity and community participation ultimately determine whether waste governance results in progress or stagnation. Keywords: Alappuzha, Banyumas, Community Participation, Political Leadership, Waste Management Tulisan ini membahas perbandingan tata kelola sampah di Banyumas, Indonesia, dan Alappuzha, India, dua kota di Global South yang sama-sama berangkat dari krisis lingkungan dan kesehatan akibat akumulasi sampah serta memiliki akses pada teknologi pengelolaan yang relatif sebanding. Kedua kota sama-sama pernah mendapatkan penghargaan internasional terkait sistem pengelolaan sampah berbasis komunitas lokal. Namun, trayektori kebijakannya berbeda. Banyumas mengalami stagnansi, sedangkan Alappuzha mengalami progresi. Dengan kerangka most similar systems design (MSSD), tulisan ini menyoroti dua aspek yang membentuk trajektori kebijakan, yaitu political continutiy dan institusionalisasi partisipasi komunitas. Berdasarkan hal tersebut, Alappuzha berhasil menjadikan krisis sebagai momentum reformasi berkelanjutan dengan mengandalkan kepemimpinan politik yang stabil dan koperasi perempuan Kudumbashree, yang mampu mentransformasi protes warga menjadi partisipasi yang lebih formal. Sebaliknya, Banyumas mengalami stagnasi karena reformasi kebijakan masih bergantung pada kepemimpinan politik individual dan partisipasi komunitas yang masih terfragmentasi. Minimnya pelembagaan membuat capaian mudah terhenti. Temuan ini menegaskan bahwa meskipun titik awal serupa, kapasitas politik dan partisipasi menentukan apakah reformasi menghasilkan progresi atau stagnasi. Kata-kata Kunci: Alappuzha, Banyumas, Partisipasi Komunitas, Kepemimpinan Politik, Pengelolaan Sampah